CRYSTALLIZATION IN ELECTRIC FIELD AS THE WAY OF CONTROL OF EXPLOSIVE SENSITIVITY OF ENERGETIC MATERIALS - V. I. Krasheninin; E. G. Gazenaur; L. V. Kuz’mina; A. S. Zverev; N. V. Gazenaur (Вестник Кемеровского государственного университета, 2015)
The paper continues the cycle of works on the analysis of intercommunication between the terms of height and reactionary ability of power materials on the example of threadlike crystals of silver azide. The paper presents the results of researching explosive decomposition of threadlike crystals of silver azide grown in the electric field, both at laser initiation (impulse by duration of 10 ns of the first accordion of 1064 nm YAG : Nd3+ of laser) and action of permanent electric-field tension of 300 кV/m. Control of admixture of the investigated materials was carried out by atomicemission method of analysis (atomicemission spectrometer with the inductively constrained plasma of iCAP 6500) ; individual edge distributions, local and general density of distributions were measured by means of optical microscope. An explosive sensitiveness was determined as the time of delay of explosion, at which it is possible to fix the fact of explosion of the standard determined on a flash or acoustical signal with the 50 % probability. The use of technology of growing threadlike crystals of silver azide allowed managing their explosive sensitiveness in the weak electric field (in the range of 10-4 ÷10 V/m) designing the imperfect and dispersible structure of these materials. Practical meaningfulness of work is determined by the possibility of using the experimental results for the purposeful management of the stability of threadlike crystals of silver azide, and also that of the explosive materials made on their basis.